Angiotensin-II stimulating vs. inhibiting antihypertensive drugs and the risk of Alzheimer's disease or related dementia in a large cohort of older patients with colorectal cancer - Du, Xianglin L.; Li, Zhuoyun; Schulz, Paul E. (Frontiers in Cardiovascular Medicine, 2023)
Background: Several previous studies showed that patients who received angiotensin II–stimulating antihypertensive medications had a lower incident dementia rate than those angiotensin II–inhibiting antihypertensive users, but no study has been conducted in long-term cancer survivors. Objectives: To determine the risk of ADRD associated with the types of antihypertensive medications in a large cohort of survivors with colorectal cancer in 2007-2015 with follow-up from 2007 to 2016. Methods: We identified 58,699 men and women with colorectal cancer aged 65 or older from the Surveillance, Epidemiology, and End Results (SEER) - Medicare linked database in 17 SEER areas in 2007-2015 with follow-up to 2016, who were free of any diagnosed ADRD at the baseline (within 12 months prior to and 12 months after the date of diagnosis for colorectal cancer). All patients who were defined as having hypertension by ICD diagnosis code or received antihypertensive drugs during this baseline 2-year period were classified into 6 groups based on whether they received angiotensin-II stimulating or inhibiting antihypertensive drugs. Results: Crude cumulative incidence rates of AD and ADRD were similar between those who received angiotensin II–stimulating antihypertensive medications (4.3% and 21.7%) and those receiving angiotensin II–inhibiting antihypertensive medications (4.2% and 23.5%). As compared to patients who received angiotensin II–stimulating antihypertensive drugs, those who received angiotensin II–inhibiting antihypertensives were significantly more likely to develop AD (adjusted hazard ratio: 1.15, 95% CI: 1.01-1.32), vascular dementias (1.27, 1.06-1.53), and total ADRD (1.21, 1.14-1.28) after adjusting for potential confounders. These results remained similar after adjusting for medication adherence and considering death as a competing risk. Conclusions: The risk of AD and ADRD in patients with hypertension who received angiotensin II–inhibiting antihypertensive medications was higher than in those receiving angiotensin II–stimulating antihypertensive drugs in patients with colorectal cancer.